Cutting Parameters Optimization in CNC Turning Operation for Controlled Surface Roughness and Higher Material Removal Rate using Design of Experiment Approach: A DOE Approach for Optimizing Cutting Conditions in CNC Turning Operation (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Obtaining controlled surface roughness and maximum Material Removal Rates (MRR) is an essential prerequisite for any unmanned computer numeric controlled (CNC) machinery. In the present work, it is observed that, using design of experiment (DOE) approach, the quality of surface finish and MRR can be achieved within a reasonable degree of accuracy by taking highly affecting independent parameters into account.In the present paper, an attempt has been made to optimize the cutting conditions to get desired surface roughness and higher MRR in turning of 8011 Aluminium Alloy. The experiments were designed using Taguchi design of experiment approach in which (33) 27 experimental runs were conducted for all the combinations of cutting parameters. The orthogonal array, signal to noise ratio and analysis of variance (ANOVA) was employed to study the performance characteristics at different conditions. Three parameters were chosen i.e. spindle speeds, depth of cut and feed rates.